Career Development and Work Environment's Impact on Performance via Job Satisfaction - I Komang Suwirta; Ida Ketut Kusumawijaya; I Made Rimanta; Chanda Chansa Thelma (Management Department Universitas Islam Negeri Sumatera Utara, 2025)
This study examines the effect of career development and work environment on employee performance, mediated by job satisfaction, at Puskesmas Abang I, Karangasem Regency. Using a census method, the entire population of 61 employees was selected as the sample. Data were analyzed through validity and reliability testing, classical assumption testing, and path analysis. The findings reveal that both career development and work environment significantly and positively affect job satisfaction and employee performance. Moreover, job satisfaction itself has a direct positive impact on performance. The mediating role of job satisfaction is confirmed, as it significantly transmits the effects of both career development and work environment on employee performance. These results highlight the strategic importance of fostering employee satisfaction to enhance overall performance outcomes. It is recommended that management prioritize structured career advancement programs, improve workplace conditions-particularly occupational safety through adequate personal protective equipment (PPE), and establish transparent promotion systems. Additionally, performance can be strengthened by implementing clear standard operating procedures (SOPs). These implications emphasize the need for an integrated human resource development approach to sustain and improve institutional service quality in public health centers. Keywords: Career Development, Job Satisfaction, Performance, Work Environment